2021
DOI: 10.1001/jamanetworkopen.2021.22269
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Colorectal Cancer Screening Test Among Individuals With Average Risk

Abstract: IMPORTANCE Colorectal cancer (CRC) screening reduces CRC incidence and mortality. It is important to examine screening patterns over time, including after the introduction of new screening modalities.OBJECTIVE To compare use of CRC screening tests before and after the availability of the multitarget stool DNA (mt-sDNA) test, given that endorsed options have changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The current study adds to the literature by including robust population estimates overall and by age groups obtained from a larger clinical database. Other real-world studies have also reported increased utilization of mt-sDNA tests since its availability in the US starting in 2015 ( Finney Rutten et al, 2020 , Fisher et al, 2021 , Limburg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…The current study adds to the literature by including robust population estimates overall and by age groups obtained from a larger clinical database. Other real-world studies have also reported increased utilization of mt-sDNA tests since its availability in the US starting in 2015 ( Finney Rutten et al, 2020 , Fisher et al, 2021 , Limburg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…Currently, colonoscopy is the gold standard for CRC detection, but this method is invasive procedure with high risk of complications, which limit its widely application in the clinical setting [ 3 ]. Fecal occult blood test (FOBT) or fecal immunochemical test (FIT) is widely used in the clinical setting due to its low cost and non-invasiveness, whereas the sensitivity and specificity of them alone is relatively low and is affect by many confounders [ 4 , 5 ]. Some tumor biomarkers, such as carcinoembryonic antigen (CEA) and carbohydrate antigen-199 (CA199), are also used to diagnose CRC, but the diagnostic accuracy remain unsatisfactory and they were not recommended for CRC screening in current clinical guideline [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recommended screening methods include colonoscopy as well as stool-based tests, such as the fecal immunochemical test (FIT) and the multitarget-stool DNA (mt-sDNA) test. Use of these stool based tests for initial screening, the mt-sDNA in particular, has increased in the past few years ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of these stool based tests for initial screening, the mt-sDNA in particular, has increased in the past few years. (4) Stool tests were developed to detect early stages of CRC as well as precancerous polyps which can then be removed during subsequent colonoscopy, which should be performed for all patients with positive stool tests. Past research has found that patients with either positive FIT or positive mt-sDNA tests are more likely to have polyps found during colonoscopy than those without preceding stool tests.…”
Section: Introductionmentioning
confidence: 99%